COMPARATIVE EFFECTS OF A CHARACTER-BASED 3P INTERVENTION AND CONVENTIONAL PARENTING GUIDANCE: A TWO-GROUP PRETEST–POSTTEST STUDY - Choiriyah Widyasari; Tri Asmawulan; Sri Katoningsih (PUPIL: International Journal of Teaching, Education and Learning, 2026)
Parents come from diverse parenting backgrounds, yet they often face similar challenges in implementing positive parenting practices. This situation is commonly associated with limited knowledge and skills related to appropriate child-rearing strategies. This study aimed to examine the effectiveness of a character-based Positive Parenting Program (3P) in improving the parenting quality of parents of early childhood children. The study employed an experimental approach using a two-group pretest–posttest design. The research was conducted in four kindergartens in Surakarta, involving 60 parents/guardians from TK Aisyiyah Pajang, TK Aisyiyah Kartasura, TK Darussalam, and TK Intan Permata. Participants were selected through random sampling and assigned to two treatment conditions: group X received the 3P intervention delivered in group sessions, while group Y received conventional parenting guidance. The main instrument was a questionnaire developed from the 3P program materials, supported by interviews and observations. Data were analyzed using t-tests to examine pre–post differences and between-group differences. The results indicated that pretest mean scores were comparable between group I (M = 19.35) and group II (M = 19.67). At posttest, the group receiving the 3P program demonstrated a higher increase (M = 24.75) than the conventional parenting group (M = 20.28). These findings suggest that the character-based 3P program is more effective in enhancing parents’ understanding of positive parenting and improving parenting quality in early childhood contexts.